Long-term consequences of reduced availability and compensatory supplementation of sialylated HMOs on cognitive capabilities - Pisa, Edoardo; Traversa, Alice; Caputo, Viviana; Ottomana, Angela Maria; Hauser, Jonas; Macrì, Simone (Frontiers in Cellular Neuroscience, 2023)
Breast milk (BM) is the optimal source of nutrition for mammals’ early life. It exerts multiple benefits, including the development of cognitive capabilities and protection against several diseases like obesity and infection of the respiratory tract. However, which components of BM are involved in individual development has remained elusive. Sialylated human milk oligosaccharides (HMOs) may constitute a valid candidate, whereby they represent the principal source of sialic acid and act as building blocks for brain development. We hypothesize that the reduced availability of two HMOs, sialyl(alpha2,6)lactose (6’SL) and sialyl(alpha2,3)lactose (3’SL), may impair attention, cognitive flexibility, and memory in a preclinical model and that the exogenous supplementation of these compounds may contrast the observed deficits. We evaluated cognitive capabilities in a preclinical model exposed to maternal milk containing reduced concentrations of 6’SL and 3’SL during lactation. To modulate their concentrations, we utilized a preclinical model characterized by the absence of genes that synthesize 3’SL and 6’SL (B6.129-St3gal4tm1.1Jxm and St6gal1tm2Jxm-J, double genetic deletion), producing milk lacking 3’SL and 6’SL. Then, to ensure exposure to 3’SL-6’SL-poor milk in early life, we adopted a cross-fostering protocol. The outcomes assessed in adulthood were different types of memory, attention and information processing, some of which are part of executive functions. Then, in the second study, we evaluated the long-term compensatory potential of the exogenous oral supplementation of 3’SL and 6’SL during lactation. In the first study, exposure to HMO-poor milk resulted in reduced memory and attention. Specifically, it resulted in impaired working memory in the T-maze test, in reduced spatial memory in the Barnes maze, and in impaired attentional capabilities in the Attentional set-shifting task. In the second part of the study, we did not observe any difference between experimental groups. We hypothesize that the experimental procedures utilized for the exogenous supplementation may have impacted our ability to observe the cognitive read-out in vivo. This study suggests that early life dietary sialylated HMOs play a crucial role in the development of cognitive functions. Future studies are needed to clarify if an exogenous supplementation of these oligosaccharides may compensate for these affected phenotypes.